Offshore Sea Life ID Guide : West Coast - Howell, Steve N. G.; Sullivan, Brian L., 1971- (Book collections on Project MUSE., 2015)
Two-thirds of our planet lies out of sight of land, just offshore beyond the horizon. What wildlife might you find out there? And how might you identify what you see? This Offshore Sea Life ID Guide, designed for quick use on day trips off the West Coast, helps you put a name to what you see, from whales and dolphins to albatrosses, turtles, and even flyingfish. Carefully crafted color plates show species as they typically appear at sea, and expert text highlights identification features. This user-friendly field guide is essential for anyone going out on a whale-watching or birding trip, and provides a handy gateway to the wonders of the ocean. First state-of-the-art pocket guide to offshore sea lifeOver 300 photos used to create composite plates Includes whales, dolphins, sea lions, birds, sharks, turtles, flyingfish, and moreAccessible and informative text reveals what to look for Great for beginners and experts alike.